KONSEP KEINDAHAN BUDAYA RUPA DALAM NASKAH SUNDA KUNO - Dr. Jamaludin M,Ds (Jurnal Budaya Nusantara, 2018)
Some ancient Sundanese texts that have been traced are Sewaka Darma (kropak 408) which contains theconcept of visual beauty (appearance) in various contexts ie place or environment in the form of a garden by making the composition or composition of various types of plants both flowering and which is not. The diversity of ornamental plants is characterized among others by the shape of the leaves, the shape and color of flowers, and the height of each plant. The beauty in a metaphysical context is also found in relation to death. Death is a perfect beauty. The image of beauty of the palace and the state of heaven or of the gods is depicted in the form of a palace construction which uses precious metals of gold, silver, as well as metals such as iron which are processed into beauty. Some ancient Sundanese texts that have been traced are Sewaka Darma (kropak 408) which contains the concept of visual beauty (appearance) in various contexts ie place or environment in the form of a garden by making the composition or composition of various types of plants both flowering and which is not. The diversity of ornamental plants is characterized among others by the shape of the leaves, the shape and color of flowers, and the height of each plant. The beauty in a metaphysical context is also found in relation to death. Death is a perfect beauty. The image of beauty of the palace and the state of heaven or of the gods is depicted in the form of a palace construction which uses precious metals of gold, silver, as well as metals such as iron which are processed into beauty.